2011
DOI: 10.1038/labinvest.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Regressed lymphatic vessels develop during corneal repair

Abstract: The fate of newly synthesized lymphatic vessels induced by inflammation is poorly understood. To address this question, we designed experiments to determine the morphologic, phenotypic, and functional differences in regressing lymphatic vessels in the context of corneal recovery after an inflammatory response. A suture removal modification was used to induce corneal recovery after suture induced inflammation. We identified an increase in markers of corneal inflammation in sutured cornea that resolved in 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The extent and duration of lymphangiogenesis are determined by balances between lymphangiogenic factors and antilymphangiogenic factors. 89, 90 …”
Section: Lymphangiogenesismentioning
confidence: 99%
“…The extent and duration of lymphangiogenesis are determined by balances between lymphangiogenic factors and antilymphangiogenic factors. 89, 90 …”
Section: Lymphangiogenesismentioning
confidence: 99%
“…Its expression was also demonstrated in lymphatic vessels of the dura mater surrounding the optic nerve and in a nonvascular pattern in the arachnoid mater . Under inflammatory conditions, podoplanin has been described in the anterior orbital adipose tissue and in the cornea during wound healing and neovascularization (Fogt et al, 2004;Kelley et al, 2011;Regina et al, 2007).…”
Section: Expression Of Podoplanin In Human Eyesmentioning
confidence: 99%
“…We and others have previously shown that sutures induce lymphangiogenesis from the corneal limbus and that suture removal stimulates wound recovery and lymphatic vessel regression [21]. Suture placement may transect or induce neuropraxia in a subset of corneal nerves.…”
Section: Discussionmentioning
confidence: 92%
“…During homeostasis, the corneal vasculature is limited to a peri-corneal limbal arcade. Angiogenesis and lymphangiogenesis from the limbus can be stimulated experimentally using suture-induced inflammation [21], [22]. In this work corneal sutures were used to induce initial inflammation; suture removal stimulated wound recovery; and replacement of corneal sutures induced recurrent inflammation.…”
Section: Introductionmentioning
confidence: 99%